Cartografia de uma retórica emancipatória: a viagem pelo olhar de Cecília Meireles, Margaret Ursula Mee e Virginie Hériot - Giselle Aparecida da Luz (2021)
Mapping the experiences of women who dared to travel, in the context of the Twentieth Century, questioning the discourses that silenced and erased the plural identities of women’s travelers, this is the belt on which we seek to place ourselves.Therefore, this research aims to analyze the emancipatory route of Cecília Meireles (1998), Margaret Ursula Mee ([2009] 2010) and Virginie Hériot (1933) through their travels.To this end, we will take ethos as the central axis as well as the narrative techniques and the pathemic effects as the underlying axes.The theoretical basis come from Amossy (2006, 2010), Charaudeau (2007b), Galinari (2012, 2014), Maingueneau (1984, 2005, 2008) and Mendes (2011, 2012) regarding the rhetorical appeals; the notion of tone from Auchlin (2001); the contributions from Charaudeau (2007a) about socio-discursive imaginary; the studies of Bauman (2005), Hall (2006) and Kauffman (2001, 2008) about identity; the contributions from Authier-Revuz (1982, 1990) with respect to the use of discursive heterogeneity; the investigations of the role of the narratee in the discursive construction proposed by Charaudeau ([1983], 2010), Machado & Mendes (2013), Peytard (1983) and Vasconcellos (2005); as well as the work of Genette (1995) in relation to the narrative voice and the term focalisation. The analysis of our corpus, showed a recurrence of the traveling narrator's ethé through three axes: how these travelers transit by the world, in which we have the discursive construction of the explorer ethos in the three traveling narrators; as well as the traveler ethos, both in Cecília Meireles and Virginie Hériot; and the persistent ethos in Margaret Mee and Virginie Hériot. The second axis concerns how they perceive the world, through the discursive construction of the benevolent ethos, in the three studied writers; the conservationist ethos in Margaret Mee; and the intellectual ethos in Cecília Meireles and Margaret Mee. Finally, the last axis shows how they are seen by the world, through the discursive construction of the legitimacy ethos observed in the three travelers who served as the basis for our research. The studies also demonstrate the use of the narratee through rhetorical questions, the use of the vocative and the use of second-person pronouns.Through our analysis about the travel narratives of Cecília Meireles, Margaret Mee and Virginie Hériot we were able to verify that, for women, traveling is an act of resistance and questioning the sexist status quo, which restricted women to private space. For these traveling women, narrating implies becoming aware of their existence in the world and claiming their rights.